Unveiling the Blockchain Intention-Behavior Gap Among Young Developers - Suwarno, Suwarno; Yoprisyanto, Josua; Aklani, Syaeful Anas (Journal of Applied Informatics and Computing, 2026)
This study assesses the factors influencing blockchain technology acceptance among young developers in Batam, Indonesia, with a specific focus on comparing two distinct behaviors: using blockchain-based applications and engaging in blockchain development. Data were collected through a survey of 215 young developers and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The main outcomes reveal two fundamentally different adoption pathways. The intention to use blockchain applications is primarily driven by personal engagement and social influence, reflecting a "hype-driven" interest, and this intention strongly translates into actual usage behavior. Conversely, the model demonstrates a complete failure to explain development behavior, revealing a significant intention-behavior gap where the intention to develop shows no significant effect on actual development activities. The study concludes that for this demographic, hype-driven interest is sufficient for superficial application adoption but wholly inadequate for fostering development capabilities. Substantive adoption requires more than social trends; therefore, industry and educational focus should shift from promoting hype to enhancing technical literacy and demonstrating tangible use cases to bridge the gap from interest to competence.